Critérios de codificação da lesão de cárie X Decisão de tratamento - Nogueira, Vinícius Krieger Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The overall aim of this study, divided into two evaluations (Chapters 1 and 2) was to evaluate the ease of application of two caries coding criteria, ICDAS (IC) and Nyvad (NY) and type of treatment decision proposed by dental students. In chapter 1, twenty-four students from the Faculty of Dentistry of Araraquara (FOAr) divided by two levels of experience - twelve undergraduate students (G) and twelve postgraduate (PG) - were distributed among the coding criteria (IC or NY) resulting in four groups (n = 6). Students performed two evaluations of 77 photographs with one week interval between them, in wick codified the caries lesions and indicated treatment (DT). The reproducibility was calculated by Kappa unweight coefficient. Sensitivity, specificity and Area under the ROC curve represented accuracy values and treatment decisions were expressed by contingency table. Good reproducibility was observed for IC values, which are applied up correctly by G and PG, both for caries lesions and to DT. The Nyvad criteria were complex to G, but showed better correlation with DT between PG. In chapter 2, four students (G) divided into two groups (IC or NY) evaluated clinically ten patients aged between 5-12 years of regular treatment at the Clinic of pediatric dentistry of FOAr. 300 sites were predetermined to codify as the criteria and DT in two evaluations with an interval of one week. Kappa coefficient unweights, Spearman correlation, sensitivity, specificity, and area under the ROC curve were calculated and treatment decisions were expressed by contingency table. Both criteria showed good reproducibility for examiners and good results for detection of early and dentin lesions. IC and NY criteria were effective for caries detection and classification and were observed a correct allocation of DT helped by criteria.

O objetivo geral desse estudo, dividido em duas avaliações (capítulos 1 e 2), foi analisar a facilidade de aplicação de dois critérios de codificação de lesão de cárie, Nyvad (NY) e ICDAS (IC), e o tipo de decisão de tratamento proposto por estudantes de odontologia. No capítulo 1, vinte e quatro estudantes da Faculdade de Odontologia de Araraquara (FOAr) divididos por dois níveis de experiência - doze graduandos (G) e doze pós-graduandos (PG) - foram distribuídos entre os critérios de codificação (IC ou NY) resultando em quatro grupos (n=6). Os alunos realizaram duas avaliações, com intervalo de uma semana entre elas, de 77 fotografias, nas quais, codificaram a lesão e indicaram um tratamento (DT). A reprodutibilidade foi calculada pelo Coeficiente Kappa não ponderado. Sensibilidade, especificidade e área sob a curva ROC representaram valores de acurácia e as decisões de tratamento foram expressas por tabela de contingência. Bons valores de reprodutibilidade foram observados para IC, sendo estes corretamento aplicados por G e PG, tanto para determinação da lesão quanto na DT. Os critérios Nyvad foram complexos para G, mas apresentaram melhor correlação com as DT entre os PG. No capítulo 2, quatro alunos G divididos em dois grupos (IC ou NY) avaliaram clinicamente dez pacientes de idade entre 5 a 12 anos em tratamento regular na clinica de odontopediatria da FOAr. 300 sítios foram pré-determinados para classificação quanto aos critérios e a DT em duas avaliações com intervalo de uma semana. Coeficiente Kappa não ponderado, correlação de Spearman, sensibilidade, especificidade e área sob a curva ROC foram calculados e as decisões de tratamento foram expressas por tabela de contingência. Ambos os critérios apresentaram boa reprodutibilidade para os examinadores e bons resultados para detecção de lesões iniciais e em dentina... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Cárie dentária; Diagnóstico; Educação em Odontologia